Two-epoch cross-sectional case record review protocol comparing quality of care of hospital emergency admissions at weekends versus weekdays. Issue 12 (22nd December 2017) - Bion, Julian; Aldridge, Cassie P; Girling, Alan; Rudge, Gavin; Beet, Chris; Evans, Tim; Temple, R Mark; Roseveare, Chris; Clancy, Mike; Boyal, Amunpreet; Tarrant, Carolyn; Sutton, Elizabeth; et al.
Abstract : Introduction: The mortality associated with weekend admission to hospital (the 'weekend effect') has for many years been attributed to deficiencies in quality of hospital care, often assumed to be due to suboptimal senior medical staffing at weekends. This protocol describes a case note review to determine whether there are differences in care quality for emergency admissions (EAs) to hospital at weekends compared with weekdays, and whether the difference has reduced over time as health policies have changed to promote 7-day services. Methods and analysis: Cross-sectional two-epoch case record review of 20 acute hospital Trusts in England. Anonymised case records of 4000 EAs to hospital, 2000 at weekends and 2000 on weekdays, covering two epochs (financial years 2012–2013 and 2016–2017). Admissions will be randomly selected across the whole of each epoch from Trust electronic patient records. Following training, structured implicit case reviews will be conducted by consultants or senior registrars (senior residents) in acute medical specialities (60 case records per reviewer), and limited to the first 7 days following hospital admission. The co-primary outcomes are the weekend:weekday admission ratio of errors per case record, and a global assessment of care quality on a Likert scale. Error rates will be analysed using mixed effects logistic regression models, and care quality using ordinal regression methods. Secondary outcomes include error typology, error-related adverse events and any correlation between error rates and staffing. The data will also be used to inform a parallel health economics analysis. Ethics and dissemination: The project has received ethics approval from the South West Wales Research Ethics Committee (REC): reference 13/WA/0372. Informed consent is not required for accessing anonymised patient case records from which patient identifiers had been removed. The findings will be disseminated through peer-reviewed publications in high-quality journals and through local High-intensity Specialist-Led Acute Care (HiSLAC) leads at the 121 hospitals that make up the HiSLAC Collaborative.